RANCANG BANGUN E-SUPPLY CHAIN MANAGEMENT SYSTEM PADA BRIGHT GAS PERTAMINA MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) - Ngemba, Hajra Rasmita; Syahrullah, Syahrullah; Indrajaya, Muhammad Aristo; Hendra, Syaiful; Lakatjinda, Adiatma (Fakultas Teknik, Universitas Tadulako, 2021)
Proper handling of problems is needed to support distribution activities. E-SCM or Electronic Supply Chain Management is a collaborative use of technology and strategic management to improve speed, performance, real-time monitoring of business processes aimed at integrating combined productive capacity and other resources in a supplier network system (Supply Chain System) through technology. Internet. The development of this system uses an extreme programming model by building Android-based applications that can only be run on mobile devices using at least the Android 5.0 Lollipop operating system. System testing will be tested with Blackbox and User Acceptance. The results of this study are the distribution system design with DRP can minimize the number of orders because the number of orders is optimal so that orders do not need to be made every week.